Meningitis caused by Pseudomonas maltophilia. Issue 9 (September 1975) - Patrick, S; Hindmarch, J M; Hague, R V; Harris, D M
Abstract : A case of meningitis caused by Pseudomonas maltophilia is described, which was unusual in that it appeared to lack the predisposing factors commonly associated with this organism. Attention is drawn to the difficulties which may be encountered in the identification of Ps. maltophilia.